2017
DOI: 10.15386/cjmed-854
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Microbiota: Tracing the Culprit

Abstract: The gastric environment has been long time considered bacteria-free, but the discovery of Helicobacter pylori (H. pylori) in 1982 superseded this conception. Over the last decades new diagnostic methods have been developed, starting with culture-dependent and advancing to culture-independent ones. These modern techniques provide new insight into the composition and influence of this ecosystem on the entire gastrointestinal tract. H. pylori is no longer considered the only microorganism in the stomach, other no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 84 publications
1
24
0
1
Order By: Relevance
“…Using culture-independent methods of analysis, evolving data show that H. pylori is not the only inhabitant of the gastric mucosa. Since the first internal biogeographic map of the human stomach was completed by Bik et al (2006) , the disruption of human gastric microbiota has been identified as a trigger of gastric diseases, especially gastric cancer ( Petra et al, 2017 ). However, the changes in gastric microbiota in metabolic disorders remain largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Using culture-independent methods of analysis, evolving data show that H. pylori is not the only inhabitant of the gastric mucosa. Since the first internal biogeographic map of the human stomach was completed by Bik et al (2006) , the disruption of human gastric microbiota has been identified as a trigger of gastric diseases, especially gastric cancer ( Petra et al, 2017 ). However, the changes in gastric microbiota in metabolic disorders remain largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence suggests that other microorganisms exhibit a role in the pathophysiology of gastric cancer. This so called non- Helicobacter pylori bacteria that are enriched in a hypoacidic environment could potentially trigger carcinogenesis via different mechanisms, such as producing toxic metabolites, promoting inflammation, modifying stem cell dynamics, and stimulating cell proliferation ( 139 ). A recent study of the stomach microbiota in patients with gastric cancer revealed similarities with the stomach microbiota of patients with dyspepsia and a normal gastric mucosa ( 140 ).…”
Section: Gut Microbiota and Immune System Interactions In Cancermentioning
confidence: 99%
“…The role of microbiome in disease development, progression, and therapy are becoming increasingly clear. While this became apparent in colon cancer and other colonic disorders like inflammatory bowel disease where the bacterial population in the gut has direct influence on the inflammatory milieu of the disease, its influence in other diseases is only starting to be acknowledged [16,19,47]. Changes in gut microbiome have now been associated with therapeutic response in melanoma [29,32], hepatocellular carcinoma, [24] and even in PDAC [26,28].…”
Section: Discussionmentioning
confidence: 99%
“…Initial studies of the gut microbiome focused primarily on colon cancer, however, recent studies have shown that microbial changes are associated with development of melanoma [14][15][16], gastric cancer [17][18][19], lung cancer [20] as well as PDAC [21][22][23][24][25][26][27][28]. While microbiome research has concentrated on its role in tumor progression, change in the microbiome may also serve as a potential biomarker of therapeutic response as well as early detection [29][30][31][32][33] [34,35].…”
Section: Introductionmentioning
confidence: 99%